THU0588 IGG4-Related Disease: Features and Treatment Response in An Asian Cohort. (15th July 2016) - Fong, W.; Liew, I.; Tan, D.; Lim, K.H.; Low, A.; Leung, Y.Y.
Abstract : Background: Most descriptions of IgG4-related disease (IgG4-RD) have been from Japanese and Caucasian populations. Objectives: To describe the clinical, laboratory, histological features and treatment outcomes of IgG4-RD in multi-ethnic Asian patients in Singapore. Methods: Patients diagnosed with IgG4-RD were identified from a Rheumatology and Gastroenterology patient database in a tertiary hospital. Demographics, clinical manifestations, laboratory results, disease activity, clinical outcomes and therapeutics used were derived from medical records. Disease activity was assessed by the IgG4-RD Responder Index. Results: 42 patients (76% male) were included; all had a diagnosis of IgG4-RD made by a rheumatologist or gastroenterologist experienced in IgG4-RD. 79% and 17% fulfilled the 2011 comprehensive diagnostic criteria for IgG4-RD 1 for definite and probable IgG4-RD respectively. 81% were Chinese and 19% were Malays. Mean age of the cohort was 62.7 ± 13.1 years. Mean age of diagnosis was 57.5 ± 12.8 years. Mean duration of disease was 4.5 ± 3.5 years. Common initial manifestations included jaundice (52%), abdominal pain (36%), swollen salivary glands (26%) and constitutional symptoms (21%). Only 36% had a history of allergy. 83% had ≥1 organ involvement, including autoimmune pancreatitis (67%), lymphadenopathy (45%), sclerosing cholangitis (43%), sialadenitis (31%) and dacryoadenitis (21%). 86% (6/7) of patients with isolated lesions involved only the pancreas. There was no gender difference in type of organ involvement. Erythrocyte sedimentation rate (ESR), IgG1, IgG2, IgG3, IgG4 levels were elevated in 83%, 22%, 74%, 37%, 41% of patients respectively. IgG4 levels did not correlate with ESR, age, disease duration, IgE levels and number of organs involved. The most common histopathological feature was that of >10 IgG4+ cells per high power field (66%), followed by lymphocytic infiltration (51%) and storiform fibrosis (51%). Only 7% had obliterative phlebitis. 94% (34/36) of patients were treated with moderate to high doses of glucocorticoids, including 17 patients with combination immunosuppressants. Of these, all patients responded to therapy by 3 months. With a mean follow-up of 4.8 ± 3.1 years, 69% (25/36) needed low dose of glucocorticoids to maintain disease remission. 26% had relapse of disease, of which 82% had disease recurrence in the same organs. Conclusions: Pancreatitis, lymphadenopathy and cholangitis were the commonest manifestations in Asians with IgG4-RD. All patients responded to glucocorticoid therapy by 3 months, two-thirds required maintenance therapy with glucocorticoids, and one-quarter developed relapse of disease. References: Umehara H, Okazaki K, Masaki Y, et al. Comprehensive diagnostic criteria for IgG4-related disease (IgG4-RD), 2011. Mod Rheumatol. 2012;22(1):21–30. Disclosure of Interest: None declared